Assessing patient awareness of rights and healthcare information: a cross-sectional study at JMF’s ACPM Medical College Dhule - Pande, Bhanupriya S.; Kulkarni, Pratik D.; Kulkarni, Parashar C.; Kuwar, Dhaneshwari M.; Manda, Ramchandra M. (International Journal Of Community Medicine And Public Health, 2025)
Background: Patient rights are fundamental in healthcare to ensure ethical treatment and informed decision-making. Despite legal frameworks promoting patient rights in India, awareness remains limited, especially in rural areas. This study assesses patient awareness regarding their rights, treatment costs, and healthcare information at JMF’s ACPM Medical College Dhule. Methods: A cross-sectional study was conducted at JMF’s ACPM Medical College Dhule. A total of 84 patients from different outpatient departments were surveyed using a structured questionnaire. Data were collected anonymously, ensuring confidentiality. Results: Findings indicate that a significant proportion of patients lacked awareness about their healthcare rights. In our study, 72.6% of patients did not know their doctor’s name, and 83.3% were unaware of their doctor’s qualifications. Additionally, 73.8% of patients did not know the expected cost of their treatment. Alarmingly, 89.3% of patients were unaware of their own health condition, and 85.7% had never seen a patient rights board displayed in the hospital. These findings highlight the need for improved patient education and transparent communication in healthcare settings. Conclusions: The study highlights a significant gap in patient awareness regarding their rights and healthcare costs. Targeted educational interventions and improved communication between healthcare providers and patients are needed to bridge this knowledge gap.